What Predicts Where Sex Offenders Live? An Examination of Census Tract Data in Minnesota - Clark, Valerie A.; Duwe, Grant (Criminal justice policy review, 2017)
Communities across the United States have become increasingly concerned over the presence of sex offenders in their neighborhoods. The purpose of this research is to examine the factors that are associated with the concentration of sex offenders in a large geographic area with few residency restrictions. This research also examines multiple categories of sex offenders subject to varying levels of community notification, allowing for an assessment of what, if any, effect community notification has on the residential patterns of sex offenders. Concentrated disadvantage, concentrated affluence, and housing affordability are all significant factors in explaining the concentration of multiple categories of sex offenders. Concentrated affluence relative to poverty is the most consistent predictor of sex offender concentration, revealing that more affluent communities ward off sex offender residents, regardless of community notification requirements.